Perspektif Kritik Ekologi Di Kepulauan Karimunjawa Mengenai Terumbu Karang Dalam Praktik Artistik Seni Lukis - Nur Ahmad Sofyan; Martinus Dwi Marianto; Heri Dono (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2025)
This research is motivated by the increasing degradation of coral reef ecosystems in the Karimunjawa Islands caused by unsustainable tourism practices and low ecological awareness of the community and tourists. In response to these conditions, this study utilizes painting as a medium for ecological criticism that not only conveys aesthetic value, but also contains educational and communicative messages about the marine environmental crisis. The main findings show that coral reef damage, especially in the Menjangan Kecil Island area, has experienced a significant escalation. This was revealed through field observations, interviews with local communities, and visual documentation. The forms of damage identified include coral bleaching, physical damage due to direct interaction with tourists, vandalism, and pollution from domestic waste and tourism. Through an artistic approach, the researcher translates these ecological issues into works of art that are full of symbolism and social criticism. These works act as a reflective medium that arouses public ecological awareness and builds a visual narrative about the importance of marine conservation. The contribution of this research is theoretical and practical. Theoretically, this study expands the discourse of fine art by integrating the perspective of ecological criticism into artistic practice. Practically, the results of this study can be used as an effective visual campaign media in increasing environmental literacy, especially in coastal areas and natural tourism destinations. Thus, painting has proven to have the potential as a strategic means of voicing environmental issues as well as being an alternative approach in marine ecosystem conservation efforts. This study encourages cross-field collaboration between artists, academics, and policy makers to build collective awareness of the importance of coastal environmental sustainability, especially in Karimunjawa and other similar areas in Indonesia.